An italic obsession: electoral reforms - Alessandro Chiaramonte (QOE-IJES, 2020)
The history of Italy is plenty of reforms of the electoral system. Many are those implemented since the country’s unification: from the majority system to the limited vote, from proportional representation to the majority premium in the liberal era; and, again, in the Republican era, the return to proportional representation and then the use of mixed systems, combining PR with plurality or majority premium. And many other are the reforms which, discussed and sometimes even approved, as in the case of the italicum, have remained dead letter or never saw the light. What explains this Italic obsession with the electoral systems? Why have their reforms been on the parties’ and governments’ political agenda for so long? The goal of this article is to answer these questions. In the end, electoral reforms have played as instruments of coordination and adaptation in the political strategies pursued by the parties in specific time periods and also as substitute instruments of institutional engineering in the absence of broader agreements on major constitutional reforms.